Recepcja twórczości Nikołaja Gogola we współczesnej literaturze łotewskiej - Narodowskaja, Iweta (Przegląd Rusycystyczny, 2011)
RECEPTION OF THE GOGOL’S WORKS IN THE MODERN LATVIAN LITERATURE Summary The article is devoted to the reception of Gogol’s works in the modern Latvian literature. The author of the article examines the collection of short stories The Seller of Pornographic Cards by the contemporary Latvian writer J. Einfelds. The collection offers a daring interpretation of the classical image of ‘small man’. The protagonist of the short story Mārtiņa Kreicberga vienīgā is associated in the consciousness of the writer with Akaky Akakievich Bashmachkin . The ‘small man’ of Einfelds has social characteristics, but is placed by the author-postmodernist into the erotic context. The author of the collection Erotic Novelettes and Naughty Stories creates the grotesque or parody in the post-modern manner, which excludes the possibility of interpretation of the ‘small man’ theme from the humanistic point of view. RECEPCJA TWÓRCZOŚCI NIKOŁAJA GOGOLA WE WSPÓŁCZESNEJ LITERATURZE ŁOTEWSKIEJ Streszczenie Artykuł poświęcony jest recepcji twórczości Nikołaja Gogola we współczesnej literaturze łotewskiej. Przedmiotem analizy jest zbiór opowiadań współczesnego pisarza łotewskiego Janisa Einfeldsa Sprzedawca pornograficznych kartek pocztowych, w którym mamy do czynienia z dość radykalną reinterpretacją klasycznego obrazu „małego człowieka”. Bohater opowiadania Mārtiņa Kreicberga vienīgā kojarzony jest przez autora z Akakiuszem Kamaszkinem. „Mały człowiek” Einfeldsa posiada wyraźną charakterystykę społeczną, jednak postmodernistyczny autor sytuuje go w kontekście erotycznym. Autor zbioru no-szącego podtytuł Erotyczne nowele i zbereźne historie stworzył utwory groteskowe, napisał parodię w duchu postmodernizmu, co wyklucza możliwość interpretacji podjętego przez niego tematu „małego człowieka” w humanistycznym kluczu.